An Insight ofSocio Economic Problemsof the members of SHGs: A Study of Punjab region - Sharma, Dr. Rasna; Chopra, Ms. Sheena (The journal of contemporary issues in business and government, 2021)
Self Help Groups act as major tool now a days for Financial Inclusion and Poverty Allevation. It is an efficient and effective tool for the Socio-Economic upliftment of the poor population lives in villages. This study has been conducted to address the problems of the members of SHGs in the highly populated districts of Punjab. Total of 20 SHGs were covered for the study and 250 members have been selected for questionnaire filling and personal interview. The study highlights the major problems faced by the rural poor like Social problems, financial problems, Personal problems, Economic Problems which are acting as a hurdle in Empowerment and Upliftment. For interpretation of data collected some statistical tools like percentage method and tests like Chi Square have been used to find out ifthere is any association in the selected two attributes.